Budaya Melayu Dalam Sekuel Novel “Padang Bulan” Dan “Cinta Di Dalam Gelas” Karya Andrea Hirata (Analisis Struktural) - Dewi Herlina Sugiarti (Departement of Mathematics Education, 2022)
The subject that is taken in this research is the cultural values of Malay on the sequel of “Padang Bulan” and “Cinta di Dalam Gelas” written by Andrea Hirata. This research uses qualitative technique with content analysis technique method, which described several datas on the texts of the novel correctly. The datas which has been classified will be described and explained based on the context that relates with the datas.By the result of this research, it can be assumed that there are structure and value on the sequel. First, the intrinsic and extrinsic on the structure of the sequel.